Maturidade sexual na qualidade de carne de frangos criados em sistema alternativo - Marçal, Joanna Oliveira (2021)
The aim of this study was to evaluate the sexual development of birds and correlate it with meat quality aspects of chickens raised in an alternative system in different genera. For the study, 90 birds of the Label Rouge lineage (Pescoço Pelado) were used, being 45 females and 45 males. The design used was completely randomized (DIC) arranged in a factorial scheme (2x2), with two sexes (male and female) and two categories of sexual maturity (non-mature and mature). The animals were slaughtered at five slaughter ages, 70, 90, 120, 150 and 180 days of age. First, a literature review was carried out, addressing the main aspects of chicken meat quality raised in an alternative system. Then, the physicochemical parameters, proximate composition and shelf life were evaluated. In both cuts, sexual maturity promoted an increase in the shear force, in addition to affecting the color of the meat, leading to an increase in the red content. Moisture was lower in the thigh of the birds after sexual maturity. In both cuts the fat content was higher in sexually mature females. The fatty acid profile in breast and thigh cuts was evaluated. The breast of female birds after sexual maturity had a lower content of C18:0, and sexually mature males exhibited a lower percentage of monounsaturated fatty acids. The thigh of mature female birds exhibited lower content of C20:2 and mature males showed estimated activity of elongaseC16-C18. In the breast of sexually mature birds, an increase in the amount of polyunsaturated fatty acids (mg of FA/g of fat) was observed. In the thigh, it was observed a reduction in the amount of monounsaturated in birds after sexual maturity. Sexual maturity affected the fatty acid composition of both cuts, causing an increase in polyunsaturated fatty acids in the breast and a reduction in monounsaturated fatty acids in the thigh. Finally, the profile of volatile compounds in breast and thigh sections was evaluated. 96 volatile compounds were identified among the chemical groups aldehydes, alcohols, terpenes, ketones, hydrocarbons, pyrazines, sulfur compounds, furans, esters and carboxylic acids. When evaluating the profile of volatile compounds through Principal Component Analysis (PCA) in general, in both cuts, birds after sexual maturity showed greater correlation with volatile compounds formed through lipid oxidation. It is also observed that for the other groups, terpenes, pyrazines, sulfur compounds, furans and esters, the effect of sexual maturity presented a different behavior among the evaluated birds. Thus, we can conclude that sexual maturity affected the composition of volatile compounds, in both cuts, and thus, we can state that sexual maturity alters the flavor of the meat.